2021
DOI: 10.1007/s00068-021-01632-0
|View full text |Cite
|
Sign up to set email alerts
|

Blunt popliteal artery injury following tibiofemoral trauma: vessel-first and bone-first strategy

Abstract: Purpose Blunt popliteal artery injury (BPAI) is a potentially limb-threatening sequela of tibiofemoral (knee) dislocations and fractures. Associated amputation rates for all popliteal artery (PA) injuries range between 10 and 50%. It is unclear whether PA repair or bone stabilization should be performed first. We analyzed (long-term) clinical outcomes of BPAI patients that received initial PA repair (vessel-first, VF) versus initial external stabilization (bone-first, BF). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…A high level of injury often means that the adequate collateral circulation of the affected limb is preserved less, the distal limb is severely ischemic, and the risk of amputation is high. It is recommended that the surgeon should strive to establish adequate circulation as soon as possible [27][28][29][30] and choose external xation brackets to initially x the fracture and immediately treat the blood vessels [3,[31][32][33]. For patients with low injury planes, due to the presence of more collateral circulation to provide blood for the distal ischemic limb, the risk of amputation is relatively low.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A high level of injury often means that the adequate collateral circulation of the affected limb is preserved less, the distal limb is severely ischemic, and the risk of amputation is high. It is recommended that the surgeon should strive to establish adequate circulation as soon as possible [27][28][29][30] and choose external xation brackets to initially x the fracture and immediately treat the blood vessels [3,[31][32][33]. For patients with low injury planes, due to the presence of more collateral circulation to provide blood for the distal ischemic limb, the risk of amputation is relatively low.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in cases of mild contamination and acceptable soft tissue conditions, the surgeon should try to choose a one-stage fracture internal xation surgery to facilitate early functional exercise of the knee joint after surgery [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Held et al 36 and Plancher and Siliski 37 found higher amputation rates between 10% and 25% in patients with PA injury from KD. Hundersmarck et al 38 showed positive long-term outcomes of (1) early revascularization and (2) bone stabilization before vascular repair if ischemia duration allows.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of popliteal artery injuries requires prompt and effective action to prevent further damage and potential loss of limb [4]. Diagnosis of popliteal artery injuries involves a thorough physical exam, imaging studies, and assessment of blood flow to the affected area [5].…”
Section: Introductionmentioning
confidence: 99%